1998
DOI: 10.1097/00000374-199804000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Binge Drinking to Alcohol Dependence, Other Psychiatric Disorders, and Behavioral Problems in an American Indian Tribe

Abstract: The hypothesis that binge drinking is a benign behavior not associated with alcohol dependence, other psychiatric disorders, or problem areas, in American Indians, was tested in a sample of 582 adult Southwestern American Indian males and females in large multigenerational pedigrees. All information was obtained from semistructured psychiatric interviews that were independently blind-rated for DSM-III-R diagnoses. Three main outcome measures were used: the relationship between binge drinking and (1) alcohol de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 0 publications
6
49
0
Order By: Relevance
“…Although tribes differ in the use of alcohol and drugs, several Native American communities have alcohol dependence rates that are 2 to 5 times higher than the general U.S. population (Gilder et al, 2004;Kinzie et al,1992;Kunitz et al, 1999;Mitchell et al, 2003;Robin et al, 1998). Few studies have investigated the risk factors that may contribute to the variance in these high rates of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tribes differ in the use of alcohol and drugs, several Native American communities have alcohol dependence rates that are 2 to 5 times higher than the general U.S. population (Gilder et al, 2004;Kinzie et al,1992;Kunitz et al, 1999;Mitchell et al, 2003;Robin et al, 1998). Few studies have investigated the risk factors that may contribute to the variance in these high rates of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In the small number of studies published, alcohol dependence rates have varied greatly. Depending on the tribe sampled and their sanctions concerning drinking, prevalence rates of 20% to 80% for men and 10% to 55% for women have been found (Beals et al, 2005;Gilder et al, 2004;Kinzie et al, 1992;Kunitz et al, 1999;Robin et al, 1998;Wall et al, 2003). Despite the devastating impact that alcohol has had in tribes who drink, what the risk factors are that may predispose a greater proportion of individuals in some Native American communities to develop alcohol use disorders remains unclear.…”
mentioning
confidence: 99%
“…Diagnostic differences were resolved in a consensus conference that included a senior psychiatrist experienced in diagnosis in American Indian people. Sampling strategy, interview procedure, and diagnosis protocol are summarized from Long et al (1998) and Robin et al (1998).…”
Section: Testing Instruments Interviews and Psychiatric Diagnosesmentioning
confidence: 99%
“…It has been reported that several Native American communities have alcohol dependence rates that are four or five times higher than the general US population (Kinzie et al, 1992;Robin et al, 1998;Kunitz et al, 1999;Mitchell et al, 2003;Gilder et al, 2004). Few studies have investigated illicit substance use involvement in Native American adults (Mitchell et al, 2003); however, some studies have investigated drug use in Native American adolescents.…”
Section: Introductionmentioning
confidence: 99%